Thomas Woodrow Wilson’s Contributions to Administrative Though and Its Critique: Array - Sokoh, Gbosien Chris (Journal of Danubian Studies and Research, 2020)
The intellectual root of public administration as a distinct field of study can be traced to the pioneering contributions made by Thomas Woodrow Wilson in the 1880s. It started with the publication of Wilson’s “The Study of Administration in 1887 in the Political Science Quarterly. Wilson’s famous essay and the discussion it generated were of unparallel importance to the development of public administration as a distinct field of study. In spite of its popularity and wide acceptance, Wilson’s idea has a number of serious limitations for which it has been criticized by a number of Scholars. Prominent among these scholars were Max Weber, Susan Barrett and Colin Fudge. After careful analysis, we confidently concluded that the development of public administration as a distinct discipline of study was Wilson’s ideas. The objective of this paper therefore was to carefully analyzed Wilson’s contribution to administrative thought and its criticisms.